ATAC-seq reveals the roles of chromatin accessibility in the chondrocytes of Kashin–Beck disease compared with primary osteoarthritis - Wang, Sen; Wang, Yuanji; Li, Xingyu; Yuan, Linlin; Guo, Xiong; Lammi, Mikko J. (Frontiers in Genetics, 2023)
Objective: This study aimed to investigate the roles of accessible chromatin in understanding the different pathogeneses between Kashin–Beck disease (KBD) and primary osteoarthritis (OA). Methods: Articular cartilages of KBD and OA patients were collected, and after tissue digestion, primary chondrocytes were cultured in vitro. Assay for transposase-accessible chromatin with high-throughput sequencing (ATAC-seq) was performed to compare the accessible chromatin differences of chondrocytes between KBD and OA groups. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were executed for the promoter genes. Then, the IntAct online database was used to generate networks of significant genes. Finally, we overlapped the analysis of differentially accessible region (DAR)-associated genes and differentially expressed genes (DEGs) obtained from whole-genomic microarray. Results: We obtained 2,751 total DARs, which contained 1,985 loss and 856 gain DARs and belonged to 11 location distributions. We obtained 218 motifs associated with loss DARs, 71 motifs associated with gain DARs, 30 motif enrichments of loss DARs, and 30 motif enrichments of gain DARs. In total, 1,749 genes are associated with loss DARs, and 826 genes are associated with gain DARs. Among them, 210 promoter genes are associated with loss DARs, and 112 promoter genes are associated with gain DARs. We obtained 15 terms of GO enrichment and 5 terms of KEGG pathway enrichment from loss DAR promoter genes, and 15 terms of GO enrichment and 3 terms of KEGG pathway enrichment from gain DAR promoter genes. We obtained CAPN6 and other 2 overlap genes from loss DARs-vs-down DEGs, AMOTL1 from gain DARs-vs-down DEGs, EBF3 and other 12 overlap genes from loss DARs-vs-up DEGs, and ADARB1 and other 10 overlap genes from 101 gain DARs-vs-up DEGs. These overlap genes were built into 4 gene interaction networks. Conclusion:FGF7, GPD1L, NFIB, RUNX2, and VCAM1 were the overlapped genes from the DAR-associated genes and DEGs. These genes were associated with the abnormal chondrocyte function, which may play crucial roles in different processes between KBD and OA in the way of accessible chromatin.